Peran Masyarakat dan Pemerintah dalam Mencegah Kebakaran Lahan di Kelurahan Sungai Andai Kecamatan Banjarmasin Utara - Yeni Anggriani; Arif Rahman Nugroho; Efrinda Ari Ayuningtyas; Wisnu Putra Danarto (Indo Publishing, 2026)
This research aims to: (1) identify the role of the community in preventing land fires in Sungai Andai Urban Village, (2) determine the obstacles faced by the community in land fire prevention efforts, and (3) examine the implementation of government programs in carrying out land fire prevention in Sungai Andai Urban Village.This study employs a qualitative approach with a descriptive method. The data were collected through interviews, observations, and documentation involving selected informants who possess relevant knowledge and information related to the research topic.The results of the study show that both the community and the government of Sungai Andai Urban Village play significant roles in preventing land fires. The community contributes through collective activities, environmental monitoring, and early reporting when fire indicators appear. Meanwhile, the local government plays a role by providing education, strengthening coordination with related agencies such as BPBD and the fire department, and implementing preventive programs that actively involve community participation.This research is expected to serve as an input for both the community and local government to strengthen collaboration and enhance the effectiveness of land fire prevention efforts in Sungai Andai Urban Village, thereby minimizing the negative impacts on the environment and the surrounding community